Assessment of control pollinated progenies as almond rootstocks - Mselmi Taoueb S.; Ben Hamda H.; Jraidi B.; Ouerghi I.; El Gharbi A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In order to select almond seedling rootstocks, many trials were conducted, at the Agricultural Experimental Unity located at the north east of Tunisia, to study the value as rootstocks of open pollinated almond genotypes. More vigorous and more developed seedlings with branched root system progenies were obtained. This study aimed to assess growth characteristics of almond seedlings obtained from controlled pollination. Thus, eight local genotypes: ‘G12-2’, ‘Tozeur 3’, ‘G12-4’, ‘G24-12’, ‘G24-10’, ‘G23-15’, ‘G25-6’, ‘G25-8’ and one foreign almond variety ‘Fasciuneddu’, were used as parentages in several controlled crosses. The fruit set was followed, but only two out of seven crosses carried out yielded fruits. Seeds harvested from the two crosses and a mixture of bitter almond seeds, the most popular rootstock in Tunisian nursery, used as control, were germinated and sown in plastic bags. Plant height, stem diameter at the ground level, number of shoots and distance up to the first shoot, were determined during vegetative dormancy. Statistical analysis showed significant differences between progenies derived from cross pollination and those from bitter almond seeds. A great vegetative growth was recorded on the progenies of ‘G25-6’ x ‘G25-8’. The average plant height and stem diameter at the ground level was 103.88cm and 8.95mm respectively. Moreover, these progenies showed the higher distance up to the first shoot, which facilitate the grafting. The cross made between ‘G12-2’ and ‘Tozeur 3’ has also provided homogeneous and vigorous seedlings. So these results showed that cross pollination may be used to select almond rootstock seedlings.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)